Do type A personality and neuroticism moderate the relationships of occupational stressors, job satisfaction and burnout among Chinese older nurses? A cross-sectional survey - Mengxin Lu; Feng Zhang; Xiaohong Tang; Liping Wang; Jinling Zan; Yan Zhu; Danjun Feng (BMC, 2022)
Abstract Background The high prevalence of burnout among nurses produces huge health service losses. Existing literature found that occupational stressors and low levels of job satisfaction were related to burnout, whilst personality traits such as type A personality and neuroticism influenced occupational stressors, job satisfaction, and burnout. The purpose of this study was to investigate the mediating effect of job satisfaction on the relationship between occupational stressors and burnout among Chinese older nurses, and explore the moderating effects of type A personality and neuroticism on the relationships among occupational stressors, job satisfaction and burnout. Methods A cross-sectional study was conducted in five provinces and municipalities (mainly in Shandong) in China. A total of 527 female older nurses (age≧40) were included in this study. Structural equation modelling (SEM) approach was employed to investigate the mediating effect of job satisfaction on the relationship between occupational stressors and burnout. Multi-group analysis was conducted to explore the moderating effects of type A personality and neuroticism on the relationships among occupational stressors, job satisfaction and burnout. Results Both nurses with high type A personality and high neuroticism had higher occupational stressors, higher burnout and lower job satisfaction. Occupational stressors had direct effect (β = 0.29, P = 0.001) and indirect effect mediated by low levels of job satisfaction (β = 0.25, P = 0.001) on burnout. Type A personality had significant moderated effect (P = 0.007) on the relationships among occupational stressors, job satisfaction and burnout, whereas the moderated effect of neuroticism was not significant. Conclusions Low levels of job satisfaction mediated the relationship between occupational stressors and burnout among Chinese older nurses, and both the direct and indirect effect of occupational stressors on burnout were moderated by type A personality. Hospital administrators should take specific measures such as transferring older nurses to easier positions to reduce their occupational stress, thereby increasing their job satisfaction and reducing their burnout, which is especially important for the older nurses with high type A personality.